Gender gap in the world of science - López-Izurieta, Indira (2025)
Gender equity in science remains a challenge. Despite progress, barriers persist that limit women's access and recognition in research and scientific publishing. They represent only 28.4% of researchers and face difficulties in obtaining funding, promotions, and leadership roles. From childhood, stereotypes discourage girls from pursuing STEM careers. In academia, women hold secondary roles in research and have less visibility in publications and editorial boards. The disproportion in awards and recognition highlights this inequity, as seen in the case of Esther Lederberg, whose contributions were overshadowed by her husband, who received the Nobel Prize. In healthcare, although the number of women in academic programs has increased, their presence in leadership positions and specialties such as surgery remains low. This inequality affects both their professional development and the diversity of medical research. Closing the gap requires strategies to encourage female participation in science, combat stereotypes, and ensure equitable conditions. Ensuring fair representation in editorial boards and funding is essential. Science will only reach its full potential when all voices are equally valued.